Significance estimation for large scale metabolomics annotations by spectral matching - Kerstin Scheubert (Nature Portfolio, 2017)
Matching fragment spectra to reference library spectra is an important procedure for annotating small molecules in untargeted mass spectrometry based metabolomics studies. Here, the authors develop strategies to estimate false discovery rates (FDR) by empirical Bayes and target-decoy based methods which enable a user to define the scoring criteria for spectral matching.